Impacts of traffic and street characteristics on the exposure of cycling commuters to PM2.5 and PM10 in urban street environments. (15th January 2021) - Hu, Haibin; Chen, Qinghua; Qian, Qingrong; Lin, Conghua; Chen, Yilan; Tian, Wenxin
Abstract: Cycling commuters are a large and growing group in China. Cyclists might be exposed to higher than average risks from pollution owing to their proximity to traffic. The factors affecting cyclists' exposure in urban streets include the sources of traffic and the dispersion of pollutants. This study performs cycling mobile monitoring under calm weather conditions in a central business district of Fuzhou, China. Relative exposure concentration (REC) after background correction is proposed to examine exposure level and evaluate the impacts of traffic density and composition and to identify street characteristics (built environment features and roadside vegetation) that determine the exposure level distribution between and within different street segments. The averaged REC of 10 m buffers along the route with a spatial variability between segments ranged from 1.2 to 3.5 μg/m 3 and 2.8–4.3 μg/m 3 above the background level for PM2.5 and PM10 . REC hotspots (>4 μg/m 3 ) not only appeared frequently in wide streets with larger traffic volumes, but also in narrow streets with dense trees owing to the accumulation of particles contributed from emission and road dust re-suspension caused by diesel trucks. In multivariable models, the street aspect ratio H/W and buildings spacing distance are the main factors inﬂuencing the REC variation in wide streets, whereas the leaf area index and canopy coverage percentage of the roadside vegetation explained 29–53% of the REC variation in narrow streets with dense trees. Our insights have the potential to inform traffic management and planning strategies designed to reduce cyclists' exposure to pollution in urban streets. Highlights: Cycling mobile monitoring of PM2.5 /PM10 was conducted in Fuzhou, China. Diesel vehicles can increase cyclists' exposure in narrow streets with dense trees. Buildings features affect the distribution of PM concentrations in wide streets. Lowering trees density can benefit the dispersion of pollutants in narrow streets.